2020
DOI: 10.1021/acssuschemeng.0c01609
|View full text |Cite
|
Sign up to set email alerts
|

Juggling Surface Charges of 2D Niobium Carbide MXenes for a Reactive Oxygen Species Scavenging and Effective Targeting of the Malignant Melanoma Cell Cycle into Programmed Cell Death

Abstract: There are several problems that need to be overcome to enable smooth and sustainable clinical translation of the MXene materials, including hard controllable surface chemistry. In this study, we show for the first time that, by using surface modification with poly-l-lysine (PLL), it is possible to completely invert the highly negative surface charge of the 2D niobium carbide MXenes (viz., Nb2C and Nb4C3) toward a highly positive value. Switching the surface charge of MXenes results in obtaining important biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…In such a case, mechanisms of cytotoxic action refer to cell cycle, DNA synthesis, and cellular membrane integrity [62]. From this perspective, surface chemistry of MXenes should be managed to avoid further toxic effects using redirecting into more safe surface compositions [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such a case, mechanisms of cytotoxic action refer to cell cycle, DNA synthesis, and cellular membrane integrity [62]. From this perspective, surface chemistry of MXenes should be managed to avoid further toxic effects using redirecting into more safe surface compositions [59].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the surface effects highly affect the living cells and it is closely linked to the oxidation process and decomposition to toxic oxides. In such a case, mechanisms of cytotoxic action refer to cell cycle, DNA synthesis, and cellular membrane integrity [ 62 ]. From this perspective, surface chemistry of MXenes should be managed to avoid further toxic effects using redirecting into more safe surface compositions [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the particle-like TMCs utilizing in catalytic and energy storage fields, film is another fashion of TMCs, where the solid materials have tiny dimensions in one dimension. Because the thickness is small, the proportion of surface particles is large, and the continuity of the structure is restricted by the surface interface, the properties of the thin films are quite different from those of the bulk materials including [49]: the decreases of melting point [32]; the selective projection and reflection of light [50]; the generation of surface energy level and surface magnetic anisotropy [51]; the varied critical temperature of superconductivity [52]; and the generated tunnel current in the direction of the thickness [53]. With the dimensionality decrease from three-dimensional to two-dimensional, the few-layered graphene and MoS 2 display many unique properties, which are quite different with their bulk states, such as higher carrier mobility and field modulated effect [53,54].…”
Section: Synthesis Of Transition Metal Carbidesmentioning
confidence: 99%
“…A recent study demonstrates the use of delaminated 2D Nb 2 C and Nb 4 C 3 MXenes modified with poly- l -lysine (PLL) as effective ROS scavenging agents. 105 Another study presents feasible ROS, reactive nitrogen species (RNS), and inflammatory cytokines scavengers based on 2D transition metal dichalcogenides (TMD). Delaminated 2D WS 2 , MoSe 2 , and WSe 2 nanosheets surface modified with polyethylene glycol (PEG) effectively reduced mitochondrial and intracellular ROS and RNS in inflammatory cells.…”
Section: Nanotechnology For Virus Prevention and Treatmentmentioning
confidence: 99%